Becoming an Ideologue: Social Sorting and the Microfoundations of Polarization - Craig M. Rawlings (Sociological Science, 2022)
This article elaborates and tests the hypothesis that the sociopolitical segregation of interpersonal networks (i.e., social sorting) is at the root of recent polarization trends in the United States. After reviewing recent trends, the article outlines the micro-level pathways through which social sorting along sociopolitical lines leads individuals to become more ideological in their identities and attitude structures. It then tests these pathways using panel data from the General Social Survey, which includes detailed measures of individuals’ social ties, ideological identification, and attitudes across a wide array of issues. Results show two dominant pathways through which more socially sorted individuals become more ideological: a short pathway directly linking social sorting to more extreme ideological identities, and a longer pathway linking social sorting to more extreme ideological identities through an increasingly ideological alignment of individuals’ attitude structures. The shorter pathway predominates among conservatives and the longer pathway among liberals. These micro-level pathways are shown to generalize to different macro-level polarization trends in identities and attitude structures for conservatives and liberals. Findings therefore uphold core sociological principles while providing stronger social-structural foundations for a growing body of mainly psychological research on ideological asymmetries.